Science - "Reseigh, Barbra" (Kingfisher, London, 1994)
Focusing on science, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book investigates concepts from materials, energy, electricity and magnetism, to forces, sound and music, and light and colour. Simple experiments are included.